Chemical Properties and Shelf Life of Banana (Musa sapientum L.) as Influenced by Different Postharvest Treatments - Zomo, S A; Ismail, S M; Jahan, M Shah; Kabir, K; Kabir, M H (The Agriculturists, 2015)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–>An experiment was conducted to evaluate the changes in the chemical properties of banana fruits and their shelf life as influenced by different postharvest treatments. There were two varieties viz. Amritasagar (VI) and Sabri (V2) and seven storage treatments viz.: control (open space, 30±2ºC) (T0); perforated polyethylene, 30±2ºC (T1); non-perforated polyethylene, 30±2ºC (T2); benzyl adenine (BA 30 ppm, 30±2ºC) (T3); gibberellic acid (GA3 150 ppm, 30±2ºC) (T4); benzyl adenine (BA 30 ppm, 15°C ) (T5) and gibberellic acid (GA3 150 ppm, 15°C) (T6). A factorial experiment was laid out in the Completely Randomized Design (CRD) with three replications. Data were recorded on titratable acid content, total sugar content, reducing sugar content, non-reducing sugar content, total soluble solids and pulp pH. Among the chemical parameters, total soluble solids (TSS) and pH of pulp increased while titratable acidity decreased during storage in all the treated and untreated banana fruits. Among the treatments gibberellic acid (GA3 150 ppm, 15°C) treatment exhibited the best storage performance. The treatment combinations of Sabri with gibberellic acid (GA3 150 ppm, 15°C) showed the longest shelf life (16.25 days), whereas the lowest shelf life was in Amritasagar with control (open space, 30±2ºC) treatment combination (6.78 days). The Agriculturists 2014; 12(2) 06-17 <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>